Comportamento de escolha: um estudo sobre efeito da variação simultânea da magnitude e do atraso do reforço a partir da replicação sistemática de Ferreira (2002) - Fernandes, Gisele de Lima (2005)
The present experiment is a systematic replication of Ferreira (2002) and aimed to analyze the choice behavior in typical developing children through the simultaneous variation of reinforcer magnitude and delay. The participants, 6 five to six year-old children who studied at a public state pre-school, were exposed to a computer choice task programmed in concurrent-chains schedule. In the initial link, there was a VI 15s schedule independently programmed in each component. Subsequently, in the baseline condition, each component was programmed to produce high and low reinforcer magnitude with the same delay (magnitude baseline) and long and short reinforcer delay with the same magnitude (delay baseline) and, in the experimental condition, there was a simultaneous variation of reinforcer magnitude and delay. There were 4 phases in the experimental condition, in which the short delay was kept at 5s, but the long delay was progressively increased throughout the phases (25s phase 1, 35s phase 2, 45s phase 3, 55s phase 4. The delay period was programmed in Fixed Time (FT). At the end of the Fixed Time, the reinforcement was made available. Tokens in different sizes and colors were used as reinforcers (big green token corresponded to high magnitude and small white token to low magnitude); they were produced in a FR5 schedule and were exchangeable for toys at the end of the session. Five high magnitude tokens were exchangeable for two toys and five low magnitude tokens were exchangeable for one toy. The results show that, although the children responded in the component that produced high reinforcer magnitude over the one that produced low magnitude (magnitude baseline) and in the component that produced a short reinforcer delay over the one that produced long delay (delay baseline) in most the trials of the baseline conditions, when these variables were simultaneously varied, the children responded more frequently in the component that produced higher reinforcer magnitude, although they were delayed, even with the increase up to 55s in delay through the phases. The data were discussed in terms of the possible interference of the procedures adopted and the reinforcing properties of the tokens, toys, and the response of using the computer over the choice and self-control behavior.